Use of climate smart agriculture technologies in West Africa peri-urban Sahel in Niger - Tinawaen Tambol; Emmanuel K. Derbile; Moussa Soulé (Scientific Reports)
Abstract Climate change affects peri-urban agricultural systems. However, most studies on Climate-Smart Agriculture (CSA) often focused on climate-smart villages in the Sahel region. This study investigated peri-urban farming systems in West African Sahel cities. Globally, agricultural productivity improvement requires applying technologies and resource access, particularly in dry-season farming. The achievements of Sustainable Development Goals 1, 2, 8, 12 and 13 in developing countries rely on utilising Climate-Smart Agriculture Technologies (CSAT) to address climate change, youth unemployment and food insecurity. The study employed a mixed-method research design, employing field and household surveys of 142 peri-urban smallholder farmers, key informants and desktop-based research in collecting data. The results showed that biopesticides/crop and pest management are the most used CSAT in dry-season farming (p = .002). These technologies eradicate pests and disease outbreaks of crops, vegetables and farm animals. The other technologies included fertilizer micro-dose, organic manure and compost application, flood-tolerant improved varieties, irrigation based on green energy, tele-irrigation, early maturing varieties and planting pits. These technologies were ranked 2nd, 3rd, 4th, 5th, 6th, 7th, 8th and 9th respectively, using mean weighted values. The study underpins local climate change trends and assessment, together with the availability, opportunities and implicit implications of scaling up CSAT. The study also recommends including peri-urban agriculture in climate and land use planning policy, programmes and projects in Niamey city.